Uji Organoleptik Minuman Teh Daun Sungkai (Peronema canescens) dengan Variasi Pemanis Alami - Sepriyaningsih Sepriyaningsih; Eka Lokaria; Mareta Widiya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the results of organoleptic tests and public acceptance of Sungkai leaf instant tea drinks with variations of natural sweeteners. The method used is an experimental method in the laboratory. Through this method, researchers obtained data by carrying out experiments directly at the Biology Education Laboratory, PGRI Silampari University. Then, organoleptic tests were carried out which included color, taste, aroma, and acceptability to 20 panelists. The highest average value of the color level organoleptic test is P2 (rock sugar) with a value of 3.4 (light green color). The highest average value of the aroma level organoleptic test was P0 (without sugar) with a value of 2.1 lacking Langu Sungkai. The highest average score for the organoleptic test for taste is P0 (no sugar) with a score of 3.7 (less sweet). While the highest average value of the organoleptic test for acceptability is P2 (rock sugar) with a value of 3.2 (likes). It can be concluded that people prefer sungkai tea with the addition of natural sweeteners than without sugar in terms of color, aroma, taste and acceptability. Keywords: Organoleptic, Tea, Sungkai Leaves, Natural Sweetener